Experimental and numerical study on the mechanical properties of compressively precracked sandstone repaired by grouting. (3rd October 2022) - Zhang, Guang-Sen; Xiao, Ming-Li; Zhang, Ya-Dong; Liu, Huai-Zhong; Zhuo, Li; Xie, Hong-Qiang; He, Jiang-Da
Highlights: A set of laboratory grouting devices was developed to grout the precracked rock specimen. The strength of grouted rock is observed to be determined by the interface between rock and cement. A numerical simulation method of grouting was developed based on the Fish language of PFC 2D . Abstract: Grouting is a common reinforcement method that is widely used in various geotechnical engineering applications. Studying the mechanical properties of grouted rock masses under different stress conditions is of great significance to geotechnical engineering, so a set of laboratory grouting devices was developed for this study. The mechanical properties of compressively precracked sandstone before and after grouting were studied by triaxial compression tests with different confining pressures, and the crack and cementation morphologies of precracked specimens were revealed by X-ray CT (Computed Tomography) scanning. According to the findings of the study, grouting significantly improves the integrity and mechanical properties of cracked specimens. The grouted specimens exhibit higher strengths and Mohr–Coulomb parameters ( c and φ), and these increments vary with confining pressures. The strength of grouted specimens depends mainly on the micromechanical properties of the contact surface between sandstone and cement grout. Affected by the mechanical properties of cement grout, the elastic modulus of the grouted specimens is lower than that of uncracked sandstone, and the deformation of the grouted specimen also exhibits an obvious ideal plasticity state under triaxial stress conditions. Thus, the grouted sandstone does not break suddenly. In addition, a numerical method of grouting was also developed in the PFC 2D program to investigate the micro mechanisms of fracturing and grouting sandstone. The numerical simulations represent the strength and progressive failure process of both intact and grouted specimens very well and reveal the micromechanical behaviors of the grouted rock mass.